(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The increasing cases of business failures arising from inability of business education graduates to adequately apply accounting competencies in managing businesses informed the need for this study. The purpose of the study was to determine financial accounting and auditing competencies required by business education graduates for entrepreneurship ventures. Two research questions guided the study while two null hypotheses were tested at 0.05 level of significance. The study adopted descriptive survey design. The population of the study comprised 1,809 managers of Small and Medium-scale Enterprises (SMEs) registered with Abia State Ministry of Trade and Investment. Simple random sampling technique was used to select 105 SME managers. A 28-item questionnaire tagged “Accounting Competencies Required for Entrepreneurship Ventures (ACREV)”wasused fordatacollection.The questionnaire had 5-point rating scale. The instrument was validated by three experts. The internal consistency of the instrument was established using Cronbach’s alpha method and it yielded a coefficient value of .82. Data collected for the study in respect of the research questions were analysed using mean and standard deviation while z-test was used to test the null hypotheses. Findings of the study showed that financial accounting competencies required by business education graduates for entrepreneurship ventures are ability to prepare final accounts, keep accurate financial records, journalize business transactions, among others. Also, the study showed that auditing competencies required by business education graduates for entrepreneurship ventures are ability to maintain good internal control system for the business, investigate to an acceptable level to establish conformity or nonconformity of transactions to the set rules and procedures, among others. It was concluded that business education graduates must possess financial accountingandauditingcompetenciesrequired for entrepreneurship ventures in order to manage small scale businesses successfully. Based on the findings, it was recommended among others, that business education students should be encouraged to register for professional programmes in financial accounting and auditing to help them acquire the required competencies.